E-Modul Produksi Pupuk Organik Berbasis SMS dengan Variasi Amandemen Organik untuk Sekolah Menengah Kejuruan - Ramdhani, Muhammad Jabbar; Sugiarti, Yatti; Rohmat, Farhan Ilham Wira (VOCATECH: Vocational Education and Technology Journal, 2026)
This study aims to develop an e-module on organic fertilizer production based on Spent Mushroom Substrate (SMS) with various organic amendments for vocational high school students majoring in agriculture, to support green skills and sustainable waste management. The research began with the process of producing organic fertilizer based on SMS, followed by testing its biological characteristics using Total Plate Count (TPC) test and chemical characteristics using Nitrogen, Phosphorus, Potassium (NPK) tests, followed by the development of an e-module using ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which was followed by expert validation involving subject matter, media, and language experts, as well as trials on 32 tenth-grade students majoring in Agribisnis Tanaman Pangan dan Hortikultura. The results showed that the addition of organic amendments could significantly increase microbial population with TPC test results showing that combination of SMS+floral compost had the most optimal results, namely 20 Cfu/gr×10⁶ on day 7 to 100 Cfu/gr×10⁶ on day 21. The NPK content of SMS-based organic fertilizer was also proven to meet SNI requirements, i.e., 6%/0.06, with SMS+CHMC sample showing the most optimal results in chemical parameters with the highest NPK content. Meanwhile, the results of implementation and paired t-test proved that e-module was considered very feasible, receiving a score of 86.6-96.6% from the validators and effectively improving student understanding, as seen from an increase in the spread of values seen in the boxplot diagram and significance value of the paired sample t-test, which was ≤0.05, taken from the results of students pre-test and post-test.